Allocation of cognitive resources in cognitive processing of rhythmic visual stimuli before gait-related motor initiation - Zhou, Huilin; Yan, Wenfeng; Xu, Jialin; Ma, Yehao; Zuo, Guokun; Shi, Changcheng (Frontiers in Neuroscience, 2023)
Rhythmic visual cues can affect the allocation of cognitive resources during gait initiation (GI) and motor preparation. However, it is unclear how rhythmic visual information input modulates the allocation of cognitive resources and affects GI. The purpose of this study was to explore the effect of rhythmic visual cues on the dynamic allocation of cognitive resources by recording the electroencephalographic (EEG) activity during visual stimuli. We assessed the event-related potentials (ERPs), the event-related synchronization/desynchronization (ERS/ERD), and the EEG microstates at 32 electrodes during the non-rhythmic and rhythmic visual stimuli among twenty healthy participants. The ERP results showed that C1 component was positive with rhythmic visual stimuli, and the amplitudes of N1 component was higher under rhythmic visual stimuli versus non-rhythmic counterparts. Within the first 200 ms of rhythmic visual stimuli input, the ERS of theta was well pronounced in all brain regions analyzed. The microstate results showed that rhythmic visual stimuli possessed an ascending cognitive processing while the non-rhythmic visual stimuli possessed a descending cognitive processing. Overall, these findings indicated that under rhythmic visual stimuli, the first 200 ms of visual cognitive processing consumed fewer cognitive resources, but the consumption gradually increased over time. After about 300 ms, rhythmic visual cognitive processing consumed more cognitive resources than non-rhythmic condition did. This was more conducive to the completion of gait-related motor preparation activities based on rhythmic visual information in the later period. It clarified that the dynamic allocation of cognitive resources is the key to improving gait movement based on rhythmic visual cues.